Numerical study of the deformation and fracture behavior of porous Ti6Al4V alloy under static and dynamic loading. (August 2015) - Biswas, N.; Ding, J.L.
Abstract: In a previous work, the dynamic compression behavior of Ti6Al4V with 0, 10 and 20% porosities, at the strain rate of 1 × 10 −3, 1 × 10 3, 4 × 10 3 and 8 × 10 3 /s, was experimentally characterized. The objective of this study is to use numerical simulations to gain insights on the observed material behavior and a general understanding of the dynamic responses of porous metals. The study indicates that the pore in general could serve as both a failure initiator and an inhibitor. The pore would lead to lower strength due to higher stress concentration as a result of the reduction of load bearing area and geometric discontinuity. On the other hand, the pore could also result in lower matrix stress at the onset of failure due to the reduced overall load bearing capacity. This lower stress and associated lower potential energy could lead to slower failure propagation and higher apparent ductility. The study also shows that the pore distribution and pore shape play significant role on the deformation and fracture behavior of porous material. For a fixed porosity, the more densely populated small pores could lead to faster failure propagation due to the enhancement of the failure propagation through void coalescence. However, the distribution does not seem to affect much the stress-stain response prior to the onset of failure. The effects of pore shape are similar to that porosity. Different pore shapes lead to different degrees of stress concentration and the apparent strengths. However, the higher stress concentration could also result in slower failure propagation due to the lower matrix stress and the associated potential energy at the onset of catastrophic failure. Besides pore density and morphology, matrix properties also played important roles on the response of porous metals. Although higher strength enhanced material's resistance to deformation, it could also lead to faster failure propagation once it was initiated due to the higher matrix stress. On the other hand, higher hardening rate could provide increasing resistance to failure propagation. Highlights: Pores in general could serve as both a failure initiator and an inhibitor. Pore results in lower strength due to reduced load bearing area and stress concentration. Pore results in higher ductility due to slower failure propagation as a result of lower matrix stress. Pore morphology and matrix properties play important roles on the deformation and fracture behavior of porous materials.